Examining Primary School Principals’ Instructional Leadership Practices: A Case Study on Curriculum Reform and Implementation - Moeketsi David Ralebese; Loyiso Jita; Olalekan Taofeek Badmus (Education Sciences)
This study examines how primary school principals navigate and influence curriculum reform through instructional leadership. Using a qualitative approach, data were gathered from semi-structured interviews and structured observations with three purposefully selected principals, guided by the Principal Instructional Management model. Interview questions focused on three core areas—developing the school mission, managing the instructional program, and fostering a positive school climate—allowing principals to share insights on their leadership strategies, challenges, and engagement in curriculum reform. Observations captured real-time practices, such as classroom visits, teacher interactions, and feedback sessions, to provide a comprehensive view of their instructional leadership roles. Thematic analysis revealed that principals actively shape school missions by integrating personal beliefs, educational agendas, and curriculum policy knowledge. They engage in reflective practices such as meetings and retreats to reinforce the school’s vision among teachers, manage instructional programs through routine and random checks, motivate teachers with positive feedback, and promote a positive climate by supporting social cohesion and addressing teachers’ personal needs. These findings underscore the multifaceted nature of instructional leadership, where principals balance personal convictions with policy-driven mandates. Recommendations include targeted professional development and formal policy recognition of instructional leadership to empower principals in leading reform efforts.